(untitled) (Research, Society and Development, 2022)
Based on the proposal for the elaboration of the educational product of ProEPT/Ifal, entitled “Campi Centenários do Ifal as Places of Memory and Identities”, this article goes back to a subtle memory of the Maceió (112 years old) and Satuba (110 years old) campuses, based on studies of the method of educator Paulo Freire and his notes on the oppressor-oppressed relationship, liberating education and the search for critical awareness for the formation of citizenship. Two publications on the history of these Ifal teaching units were analyzed as a comparative content between Freirean theories and the historical context of these institutions, which are: “Nos Trilhos da Memória” by Patrícia Rosalba Costa, Amanda Christine Marques and Álvaro Queiroz, a publication launched in 2012 to commemorate the 100th anniversary of Campus Satuba and, “From the School of Apprentices and Craftsmen to the Federal Institute of Alagoas”, authored by professor Irene Bonan, which was launched in 2009 to celebrate the 100th anniversary of the Maceio Campus. What is concluded is that the works of Paulo Freire, mainly “A Pedagogia do Oprimido”, not only refer us to a degrading social reality in the beginnings of public professional education, but also gave an address to student communities for effective social changes. in Brazilian education and the federal institutes were not left out of this educational context.